The Influence of Product Quality and Brand Image on Blush On Cosmetic Purchasing Decisions Madame Gie in Surabaya - Putri Setiawati; Hery Pudjoprastyono; Zawawi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and analyze the effect of product quality and brand image on the purchasing decision of Madame Gie Blush in Surabaya. The population in this study were users of Madame Gie Blush in Surabaya. The sampling method used non-probability sampling with a purposive sampling technique and obtained a sample of 60 respondents. This study uses data analysis using the component-based Structural Equation Model (SEM) method using Partial Least Square (PLS) analysis. In this study, primary data was obtained from questionnaires distributed to the respondents. The results show that product quality and brand image have a significant positive effect on purchasing decisions for Madame Gie's blush cosmetics in Surabaya.